Nucleolar Organizer Regions in Oral Squamous Cell Carcinoma - Monir Moradzadeh Khiavi; Sepideh Vosoughhosseini; Monire Halimi; Seyyed Mostafa Mahmoudi; Asghar Yarahmadi (Tabriz University of Medical Sciences, 2012)
Background and aims. Several diagnostic methods are being employed to detect benign and malignant lesions, one of which is silver nitrate staining for organizer regions. The number of nucleolar organizing regions (NORs) can be used to show the degree of cell activity or metabolism in pathologic lesions. This study was designed to evaluate NORs as determinants of precancerous and squamous cell carcinoma. Materials and methods. A silver colloid technique was applied on paraffin sections of 40 cases of oral squamous cell carcinoma and 25 cases of precancerous lesions; 15 specimens of normal epithelium were selected for the control group. After staining with silver nitrate, argyrophilic nucleolar organizer regions (AgNORs) were counted in 100 epithelial cells in three groups with the use of an oil immersion and ×1000 objective lens. One-way ANOVA and a post hoc Tukey test were used for statistical analysis. Results. The mean numbers and standard deviations of AgNORs were 1.58 ± 0.76 in normal epithelium, 2.1 ± 1.05 in precancerous lesions and 2.43 ±1.33 in squamous cell carcinoma (SCC). There were statistically significant differences in AgNORs numbers between the groups (P<0.001) and significant differences in precancerous lesions between dysplastic and non-dysplastic epithelia (P<0.001). The mean AgNORs count per nucleus increased from healthy epithelium to precancerous lesion to SCC. Conclusion. This study suggests that the silver staining technique for the detection of NORs (AgNOR) can be used to distinguish precancerous lesions and benign and malignant lesions.